An fMRI study of relative clause in comprehensive among native and non-native Malay language speaker - Sumardi, Nurul Bayti (2021)
Introduction: Sentence comprehension is a cognitively demanding process. The comprehension of complex and non-canonical sentences like relative clauses caused the activation of particular brain regions. Objectives: This study investigated whether there is functional neural activation at the frontal and temporal brain regions during the comprehension of the Malay relative clause. This study also aimed to find the differences in the activated areas among the native (L1) and non-native (L2) Malay language speakers. Methodology: This observational study was conducted at the Hospital USM Kubang Kerian, Kelantan, from December 2020 to April 2021, involving native (L1) and nonnative (L2) Malay language speakers. Four L1 (mean age = 24.2 year old, SD = 1.25) and four L2 (mean age = 23.5 year old, SD = 0.43) participated in this study. The subject relative clause (SRC), object relative clause (ORC) dan subject-verb-object (SVO) were used as study stimuli. They were asked to do a sentence-picture matching task during fMRI measurement. Results: The functional brain activation of L1 and L2 were observed and compared. The random-effect analysis (RFX) using two-way repeated measure ANOVA was conducted for the fMRI data. The main effect of the group at the puncorrected < 0.001, cluster size > 20 voxels found that the comprehension of Malay relative clauses had activated frontal and temporal brain regions in L1 and L2. The multiple comparisons of L1>L2 showed a significant difference left-lateralised in the temporo-parietal region. While for L2>L1, the significant activations were indicated distributed to the frontal, temporal, parietal, and occipital regions that lateralised to the right hemisphere. Additionally, one-way repeated measure ANOVA of reaction time in the L1 group showed no significant difference between SRC, SVO, and ORC (F(2,82) = 2.43, p = 0.094, ƞ2 = 0.056). Meanwhile, the one-way repeated measure ANOVA of reaction time in the L2 group showed no significant difference between conditions SRC, ORC, and SVO (F(2,54) = 3.13, p = 0.052, ƞ2 = 0.104). Conclusion: The findings suggested that comprehension of Malay relative clauses had caused the activation at different brain regions amongst its L1 and L2. It was also found that both L1 and L2 groups showed their preference in SRC over ORC. The findings from this study can also be applied in clinical language intervention, and it is expected to benefit children and adults with speech and language disorders.